The effect of using the problem-solving method in teaching the Elements of Art subject (Journal of the College of Basic Education, 2023)
Education, in its general concept, aims to build the human personality in an integrated manner from all mental, physical, emotional, social, behavioral aspects...etc., as it works to qualify him to acquire educational experiences, both cognitive and skillful, to help him earn a living and perform his functions in society.The interest in the educational process comes from paying attention to its elements represented by (the teacher - the learner - the curriculum - methods and methods of teaching - and other requirements).Teaching methods and methods represent one of the basic elements in the educational process, as they work to deliver experiences, educational activities, and technical skills to learners in order to help them grow properly in the light of society’s philosophy and specific educational goals. Likewise, these methods or teaching methods represent the means that convey science, knowledge, and skill to the learner whenever they are appropriate. According to the educational situation and consistent with the learner's chronological age, abilities and tendencies, the goals achieved through it were deeper and more useful.Among these methods and methods is the problem-solving method that develops the scientific thinking of the learner and brings him to a state of creativity and innovation. In his public life, he achieves a rise in his level of self-esteem, and develops his innovation factor by presenting new ideas and rearranging previous ideas.And since the Department of Art Education is one of the scientific departments in the College of Fine Arts, it aims to prepare students for the profession of teaching art education in the secondary education stages. Therefore, this department seeks to provide them with educational and artistic experiences and provide them with the necessary skills to prepare them optimally, as they are exposed during their studies to many courses. The course includes (educational, vocational, cultural, and different skills) and among these courses is Art Elements, which is a basic subject through which the student acquires the necessary skills that contribute to giving him a mental image of how to employ them in the artistic work, as it gives opportunities to students in how to think about the process Organizing those elements that make up the artistic composition, and this can only be expressed through mastering her skills.Based on that, the researcher decided to reveal the effect of using the problem-solving method (the fourth method) in teaching the Elements of Art subject and the extent of its impact on students' acquisition of artistic skills for that subject.